2017
DOI: 10.1111/trf.14369
|View full text |Cite
|
Sign up to set email alerts
|

Fetal/neonatal alloimmune thrombocytopenia due to anti‐CD36 antibodies: antibody evaluations by CD36‐transfected cell lines

Abstract: BACKGROUND: Isoantibodies against CD36 (platelet glycoprotein 4), developed in Type I CD36-deficient mothers are frequently reported as the cause of fetal/ neonatal alloimmune thrombocytopenia in the Asian population. Therefore, further detailed characterization of anti-CD36-mediated fetal/neonatal alloimmune thrombocytopenia is warranted. Here, we report the characterization of a patient with fetal/neonatal alloimmune thrombocytopenia in a Taiwanese family caused by anti-CD36 isoantibodies using a novel antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…In this study, we found that around 0.43% of Thai blood donors exhibit Type I CD36 deficiency and are therefore at risk of developing anti‐CD36 antibodies if exposed to the antigen through transfusion or pregnancy . These antibodies can cause PTR and serious FNAIT, as recently reported in different Asian populations . Indeed, a case of FNAIT has been reported in Thailand .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…In this study, we found that around 0.43% of Thai blood donors exhibit Type I CD36 deficiency and are therefore at risk of developing anti‐CD36 antibodies if exposed to the antigen through transfusion or pregnancy . These antibodies can cause PTR and serious FNAIT, as recently reported in different Asian populations . Indeed, a case of FNAIT has been reported in Thailand .…”
Section: Discussionsupporting
confidence: 63%
“…2 These antibodies can cause PTR and serious FNAIT, as recently reported in different Asian populations. 3,4 Indeed, a case of FNAIT has been reported in Thailand. 18 Based on this fact, routine diagnostics as well as treatment strategy for anti-CD36-mediated bleeding disorders with use of CD36-compatible platelets should be seriously taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Besides, the lack of such a membrane GP can also have a negative impact, because it can lead to isoimmunization in Type I deficiency, in the contexts of pregnancy, PLT transfusion, and even RBC transfusion, as RBCs are contaminated by remaining PLTs and WBCs even after centrifugation and filtration and potentially by circulating CD36-positive microparticles, a source of the plasmaderived form of soluble CD36. 20,21 Anti-CD36 isoimmunization can engender serious complications such as PLT transfusion refractoriness, 13 PTP-like syndrome, 14 and fetal or neonatal immune thrombocytopenia, 15,[22][23][24] which explains the interest of our lab in searching for CD36neg patients and their risk of immunization as well as to study the underlying molecular defects.…”
Section: Discussionmentioning
confidence: 99%